Analysis of the application of language skills and how they influence in the level of English learners of Tercero de Bachillerato General Unificado "A" at Unidad Educativa "Isabel de Godin" in the academic period november 2021- april 2022 - Cabezas Salas, Michelle Dennisse (2022)
The four language skills such as listening, reading, speaking and writing are essential to master the English language, otherwise the language learners won not be able to communicate what they think and feel just as it will not be possible for them to understand their interlocutors. Thus, it is expected language learners to be able to understand, analyze and communicate their ideas independently, for this it is necessary to develop all the skills of the language which can be achieved with the help of methodological strategies. Therefore, the objective of this research is to analyze the application of skills and how they influence the level of English of the students of Tercero de Bachillerato General Unificado “A” in the Unidad Educativa “Isabel de Godin” and accordingly thus propose methodological strategies that will contribute to the development of receptive and productive skills. This research is non-experimental and has a qualitative approach. The observation guide was used as an instrument for 30 students of said institution, which showed that most methodological strategies for the development of each of the skills are not applied, as a consequence the students cannot communicate correctly. Based on the observation, it was established that the level of English is basic-elementary, which does not correspond to age or level of study.